2022
DOI: 10.1021/acs.est.2c01728
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-Assisted Fabrication of Thin-Film Nanocomposite Membranes for Improved Solute–Solute Separation

Abstract: Efficient separation of harmful contaminants (e.g., per-and polyfluoroalkyl substances, PFASs) from valuable components (water and nutrients) is essential to the resource recovery from domestic wastewater for agricultural purposes. Such selective recovery requires precise separation at the angstrom scale. Although nanofiltration (NF) has the potential to achieve solute− solute separation, the state-of-the-art polyamide (PA) membranes are typically constrained by limited precision of solute−solute selectivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…It revealed that the average porosity of the whole active layer increased from 2.25% for M PA to ∼2.46% for M MPA (Figure S3), although no linear increase with increasing MPIP was observed. This result is due to the depth inhomogeneity with a loose structure on the top and a dense barrier segment on the bottom, , which was especially the case for the M MPA membrane, reflected by the sharp decrease in the S parameter with the increasing depth of positron detection in the polyamide active layer (Figure C), and partly because of the difference in active layer thickness among membranes. Nevertheless, these results semi-quantitatively indicated that the water permeability and likely the corresponding porosity (interpore connectivity) of the active layer were substantially improved after the introduction of MPIP with leaving ester groups.…”
Section: Resultsmentioning
confidence: 99%
“…It revealed that the average porosity of the whole active layer increased from 2.25% for M PA to ∼2.46% for M MPA (Figure S3), although no linear increase with increasing MPIP was observed. This result is due to the depth inhomogeneity with a loose structure on the top and a dense barrier segment on the bottom, , which was especially the case for the M MPA membrane, reflected by the sharp decrease in the S parameter with the increasing depth of positron detection in the polyamide active layer (Figure C), and partly because of the difference in active layer thickness among membranes. Nevertheless, these results semi-quantitatively indicated that the water permeability and likely the corresponding porosity (interpore connectivity) of the active layer were substantially improved after the introduction of MPIP with leaving ester groups.…”
Section: Resultsmentioning
confidence: 99%
“…The probable swelling and deformation of polyelectrolyte layers induced by high salinity and pressure conditions are obstacles which need to be solved for the practical applications of PEM membranes. , Large-scale fabrication of these membranes also remains a challenge. Besides the commonly used modification methods and polymer-based novel chemistry of selective layers elaborated in detail in this review, other delicate strategies (e.g., capillary-assisted IP and amine modification , ) to regulate the formation of PA membranes and exploitation of two-dimensional nanomaterials (e.g., graphene oxide, molybdenum disulfide, MXene, , etc.) as building blocks of selective layers have attracted growing research interests in recent years.…”
Section: Concluding Remarks and Research Outlookmentioning
confidence: 99%
“…Harvesting clean and safe water from municipal secondary effluent by advanced technologies has become an emerging avenue to alleviate water scarcity. 1,2 For example, photocatalysis, 3,4 electrochemical methods, 5−8 adsorption, 9,10 and membrane separation. 11,12 Among them, membrane separation is more concerned because it is free of additional reagents and secondary pollution, satisfying the carbon emission reduction demand and environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%